Determination of Radioactivity Levels in Different Mushroom Species from Turkey - PEKŞEN, Aysun; KURNAZ, Aslı; TURFAN, Nezahat; KİBAR, Beyhan (Yuzuncu Yil Universitesi Tarim Bilimleri Dergisi, 2021)
Radioactivity in the environment occur due to natural, terrestrial, extra-terrestrial factors or caused by the human activity. Food stuffs that grown in the soil which containing radioactive elements may get deposited or absorbed in the foods. Wild growing mushrooms can accumulate many types of toxicological, nutritional and radioactive elements. So, mushrooms are considered as good bio-indicators to determine the environmental pollution caused by radiations. Knowing the levels of radioactivity in the food stuffs is of great importance for the protection of human health. In this study, the active concentrations of the naturally occurring 238U, 232Th, 40K nuclides and artificially occurring 137Cs nuclide were determined and annual effective doses and excess lifetime cancer risk values were calculated in mushrooms commonly consumed by the Turkish people. 15 types of mushroom samples were collected from different locations of Turkey. The results show that the activity concentrations of 238U, 232Th, 40K and 137Cs varied from 9.2±1.6 to 75.4±8.8 Bq kg-1, 10.9±1.6 to 76.3±8.9 Bq kg-1, 925.9±29.0 to 3848.0±73.2 Bq kg-1 and 6.1±1.1 to 2824.8±79.8 Bq kg-1, respectively. The mean total annual effective dose was found to be 11.5 μSv y-1. 40K radionuclide was the highest contributor to the total annual effective dose (5.35 μSv y-1). According to these values obtained, the mean excess lifetime cancer risk (ELCR) of mushrooms was determined as 4.6 x10-5 %.
Keywords: yaşam boyu kanser riski; yıllık etkin doz; radyonüklid; annual effective dose; lifetime cancer risk; Annual effective dose; Lifetime cancer risk; Mushroom; Radioactivity; radioactivity; mantar; mushroom; Radionuclide; radyoaktivite; radionuclide; 2. Zero hunger; 15. Life on land; 3. Good health; 13. Climate action; 11. Sustainability